(untitled) (Phenomenology, Humanities and Sciences, 2025)
Considering the critical readings made by Lacanian Psychoanalysis, this article seeks to question the way in which Merleau-Ponty describes the presentation of otherness in perceptive experience and dialogue. The question addressed to Merleau-Ponty’s reflections is related to the Lacanian suspicion that, despite recognizing the inalienability of otherness, Merleau-Ponty remains attached to the belief that there may be a kind of coincidence between otherness and the subject who perceives or questions it. This would be a strategy to obscure the fact that, in his description of the carnality of perceptive and dialogical experience, Merleau-Ponty continues to orient himself from the idea of ​​the primacy of a seer, which re-edits a kind of subjectivism that has not spared even Psychoanalysis.